Superporous acrylic acid and HPMC hydrogels of mefenamic acid: Formulation, characterization and optimization by central composite design - Khan, Hafeez Ullah; Aziz, Samar; Maheen, Safirah; Khan, Ikramullah; Andleeb, Mehwish; Younis, Hina; Haider, Sajjad; Haider, Adnan; Akhtar, Muhammad Saeed; Shafqat, Syed Salman (Frontiers in Bioengineering and Biotechnology, 2022)
The purpose of the study was to devise the superporous hydrogels (SPHs) of mefenamic acid (MA) to acquire the sustained action of the MA in the body. The SPHs of MA were formulated by employing the gas blowing method. The Central composite research design (CCRD) was exploited to optimize the independent factors over dependent variables. A number of characteristics such as void fraction, surface morphology by Scanning electron microscopy (SEM) and in vitro drug release study were governed along with physico-chemical analysis by Fourier transform infrared spectroscopy (FTIR), Differential scanning calorimetry (DSC) and appraised statistically by employing the ANOVA. The comparative analgesic activity of optimized superporous hydrogel formulation SPH17 was also analyzed by using tail flick method. The FTIR and DSC studies approved the physical compatibility between the polymers and the drug. The SEM study specified micrographic insight about the structure of formed formulations comprising presence of pores, fibers and drug-hole aggregates. The SPHs were detected to be low dense as they expressed density lower than 0.75 g/cc. The decrease in concentration of the polymers and cross linker contributed towards the increase in the void fraction of the SPH formulations. The optimized formulation SPH 17 exhibited a highly sustained release of MA for up to 10 hours in the both 0.1 N HCL and phosphate buffer (66.6 %) media. The non-fickian release of drug revealed the coupling of the diffusion and polymer relaxation mechanism of the drug release from the formulations. The obtained outcomes suggested that analgesic effect of SPH 17 was significantly (p < 0.05) higher than that of simple suspension of MA and total analgesic effect duration for SPH was also doubled as compared to the duration of analgesic effect produced by drug suspension. The successfully formulated SPH with HPMC K100M as a gelling agent had sustained the action of the Mefenamic acid by improving its poor solubility and permeability and imparting increase residence time from introducing inter-penetrating polymeric network (acrylic acid) using glycerol as a cross linker which ultimately enhanced the feasibility of using SPH as oral sustained release devices particularly for gastric retention.